Jackson, Peter, Nick Stevenson, and Kate Brooks. Making Sense of Men’s Magazines. Oxford: Polity, 2001. 214 pp. - Bajner, Mária (FOCUS: Papers in English Literary and Cultural Studies, 2004)
While there are several stirring publications on women’s magazines, there is as yet a very limited number of academic studies on the men’s magazine market. The reason may be that a little more than a decade ago it was asserted that “men don’t buy magazines” (6), apart from pornography or special interest magazines on sports, photography or motoring. By the mid-nineties men’s general interest in “lifestyle” (2) magazines had become the largest and the fastest-growing sector of this dynamically growing publishing industry. The authors of Making Sense o f Men s Magazines venture upon giving an explanation for the phenomenal success of this new breed of men’s magazines, not only in commercial terms but also in terms of what their success tells us about the changing nature of contemporary masculinities, femininities, and gender roles. The book does not aim to celebrate “the new forms of masculinity”), neither does it wish to take a moralistic stance: rather, it places the issue in a wider social context, while tracing specific ways in which different individuals “make sense” of changing gender roles and relations.